Sorption-Photometric Determination Of Nickel And Cobalt Ions In The Industrial Waste Of "Olmaliq Kmk" Jsc Using Diethyl 2,2'- ((1,3,4-Thiadiazole-2,5-Diyl) Bis (Sulfandiyl)) Diacetate Organic Reagent - Mirzakhmedov Rustamjon Mirkhamidovich; Mirusmanova Farangis Boburovna; Bobojonov Khikmat Shavkatovich (Genius Publishing Group, 2023)
Currently, sorption-photometric methods are widely used in the determination of heavy metals. This method is of great importance due to its sensitivity, simplicity, and less time spent on analysis. Sorption-photometric methods, one of the most modern physical and chemical methods, are widely used. Sorption-photometry is based on measuring the light absorption of colored and colorless solutions in monochromatic light
Keywords: Sorption-Photometric; heavy metals